Managerial myopia and corporate green innovation: evidence from Chinese A-share listed firms - Wang, Rui; Zhen, Xi; Li, Lei; Ma, Xiaoyu; Ma, Shaojun (Frontiers in Physics, 2026)
Against the backdrop of escalating climate risks, firms increasingly regard green innovation not merely as a sustainability initiative but as a strategic response shaping long-term competitiveness. From a managerial decision-making perspective, this study examines how managerial myopia influences firms’ green innovation capabilities. Using panel data from Chinese A-share listed companies spanning 2013 to 2022, we employ empirical regression analyses to investigate the direct effect of managerial myopia on green innovation, as well as the moderating roles of environmental regulation and media scrutiny. The results show that managerial myopia significantly inhibits firms’ green innovation, as an excessive focus on short-term profits constrains effective resource allocation for green initiatives, thereby undermining both environmental performance and long-term sustainability. Furthermore, command-and-control environmental regulations exacerbate the negative impact of managerial myopia, whereas negative media scrutiny mitigates this effect by functioning as an external governance mechanism. A more nuanced analysis reveals that the aggravating role of command-based regulations is significant only for independent R&D and non-inventive green innovation, while media attention primarily alleviates adverse effects on independent R&D and inventive green innovation. Heterogeneity analyses further indicate that state ownership and operations in heavily polluting industries help restrain managerial myopia, partially preserving firms’ green innovation capabilities. By foregrounding managerial myopia as a key internal governance factor, this study deepens the understanding of how managerial cognition shapes corporate green innovation and offers actionable implications for policymakers, regulators, and stakeholders seeking to curb short-term managerial bias and strengthen firms’ sustainable innovation dynamics.